Implementation Of The Istihsan Method In Islamic Economic Law - Fauzi, Mohammad Yasir; Santoso, Rudi; Majdidin, Rijah Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article describes the istihsan method and examples of its application in several cases of shari'ah economic law. The approach used is an ontological, epistemological and axiological based philosophical approach which discusses the nature of istihsan, the principles of istihsan, the method of application and the impact of the istihsan method. The research method used is qualitative library research with a descriptive pattern and making the polautturats al-mu'tabaraoh as the main reference. The istihsan method was first introduced by Imam Abu Hanifah (d.767 AD) as the first absolute mujtahid imam among Muslims who managed to explore direct laws from the Al-Qur'an and Hadith. The istihsan method is basically a mujtahid with a good view of a reason in determining the legal status of a new case that has not been concretely stated in the law in the texts of the Qur'an and Hadith. In the next phase, the istihsan method received criticism from other madhab priests such as Imam Syafi'i. However, this criticism is actually just a difference of opinion in defining the istihsan in question, which in essence there is no substantial difference between them. Istihsan is widely felt in Hanafiyah fiqh texts such as in the book of al-Mabsuth by as-sarkhasi (w.483 H). In this contemporary era, istisan is very relevant to be used, especially in determining the legal status of new cases that cannot be solved using the ushul figih method of the Syafi'iyah madhab or other schools of thought.Keywords :Istihsan, Kutubut Turats, Hanafiyah Madhab